Dynamics of the Professional Orientation of the Students in the Specialty of Pre-School and Primary School Education (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2018)
The article presents the problem of the vocational orientation of students who are mastering the professions of pre-school and primary-school teachers at the Faculty of Education at Trakia University. The subject of the study is the professional orientation of students in the specialty "Pre-school and primary-school education". The object of the study is the dynamics of their career orientation from the first to the last year of their studies at the university. The aim is to establish the level of professional orientation of students mastering the teaching profession. The following research methods were used for the implementation of the so set aim: test, content analysis, pertinent analysis, longitudinal study. Presented are the results of the author's study, tracking the dynamics of the professional orientation of the students during the first and the last year of their studies in the faculty. The results indicate that the professional choice of future pedagogues is conducted in accordance with a process of realization of their professional self-identification. The young people who study Pre-school and Primary School Education choose their future profession on the basis of their high level of professional orientation. A supportive pedagogical environment in the course of their training helps to raise the level of their professional orientation.